Melanization of eggs and larvae of the parasitoid, Epidinocarsis lopezi (Hymenoptera: Encyrtidae), by the cassava mealybug, Phenacoccus manihoti (Homoptera:Pseudococcidae) - Sullivan, D.J.; Neuenschwander, Peter (Cambridge University Press, 1988)
The encyrtid wasp Epidinocarsis lopezi (De Santis) has been introduced into Africa as a biological control agent against the cassava mealybug Phenacoccus manihoti Matile-Ferrero. This host has a defense reaction against the immature parasitoid that involves encapsulation and melanization. Under laboratory conditions, 37.5% of once-stung cassava mealybugs had been parasitized, as indicated by eggs and larvae of the parasitoid in dissected hosts. Of these parasitized cassava mealybugs, 89.6% contained melanized particles (egg, partially melanized larva, internal host tissues, exoskeleton wound scars). Some of the parasitoid larvae were only partially melanized, and either freed themselves from the melanized capsule or else shed it at the next molt. By the 3rd day of their development only 12.5% were completely melanized. In cassava mealybugs with melanized host tissue but no living parasitoid, the survival of the host was not affected by the melanization. The mealybug itself sometimes shed black particles at the next molt and these were found attached to the cast skins. When superparasitized in the laboratory, 68.6% of twice-stung cassava mealybugs contained parasitoids. Mummies collected from a field experiment showed that melanization rates of mummies increased with increasing parasitization rates. Thus, melanization in the cassava mealybug was commonly triggered when E. lopezi oviposited, but this defense reaction was mostly ineffective, permitting the introduced parasitoid to be a successful biological control agent in Africa against the cassava mealybug, a major pest on this important food crop.